Vendor Business School - Wamai, Ken (CGIAR Initiative on Resilient Cities, 2023)
The Vendor Business School (VBS) comprises a total of 14 modules including entrepreneurship, business planning, marketing, customer care, record keeping, financing, and formalization of businesses. The modules will be delivered through small group meetings but with opportunities for individual coaching sessions. The tool is expected to be piloted in urban Nairobi in 2024, to assess its impact on women-run businesses, and identify areas that would need to be strengthened to improve the tool.